Radiological input during paediatric multidisciplinary team meetings and its influence on clinical patient management. Issue 2 (12th February 2016) - Llewellyn‐Jones, Glyn; Pereira, John
Abstract: Introduction: There is little information about the role of the radiologist at multidisciplinary team meetings; in particular their influence on patient management. To evaluate the influence of radiologists on clinical patient management during multidisciplinary meetings. Methods: Prospective data were collected over a 5‐week period from multidisciplinary team meetings across four paediatric clinical domains. Radiological input was recorded for each case discussion, including the type of influence and its potential effect on clinical patient management. Results: One hundred and forty paediatric cases were reviewed. Radiological advice was requested from the radiologist for 25.7% ( N  = 36) of cases. In 17.9% ( N  = 25) this advice was judged to have influenced clinical patient management. There were two cases where new imaging findings were discovered. Conclusions: Radiologists influence clinical patient management during multidisciplinary team meetings primarily by providing differential diagnoses and guidance regarding future imaging, with respect to both the necessity and the modality. Occasionally, when imaging is reviewed at these meetings, new findings are discovered that impact on patient management.